TOURIST ENTERPRISES FINANCING IN GREECE - Chryssanthi Balomenou; Panagyiotis Arsenos; Dimitris Lagos (European Regional Science Association (ERSA), 2005)
The main purpose of our paper is to examine the financing framework of the Greek tourist enterprises. More specifically, in the first part of this paper we analyze the sector of the Greek tourism market in order to be able to define its operational framework. Then, we examine the structural problems of the sector and analyze the relevant Institutional financing framework. In the second part we work out a critical assessment of the tourist enterprises existing financial framework, focussing on the financial difficulties that they face. In the last part of our paper, we set out our proposals concerning the adoption of the appropriate tourism policy that will contribute to the supporting of the aforementioned firms and especially to their access to finance (through Developmental Laws, E.U's programs, financial Institutions like Credit Guarantee Fund for Small and Very Small Enterprises, etc). The most important conclusions that come out of the whole analysis of our paper, show that the majority of Greek Tourist Industry are small enterprises that they have the same structural characteristics (e.g: seasonal bussiness, mainly situated in insular regions, stayed behind large companies in terms of productivity, technological experience, financial and other areas. Particularly, they often lack creditworthiness and have trouble securing funds needed for their business activities). Furthermore, tourist enterprises, like most small companies have only limited capital resources. So, they have to rely on banks and other financial institutions for their funds. Banks require sufficient collateral or a well-established surety for their debtors to secure a loan. The lack of such assets or appropriate surety makes it difficult for many small tourist business to obtain loans from financial houses. Thus, it is obvious that the pin pointing of the financial problems that the tourist enterprises face, facilitates the planing of the appropriate mix of tourism policy measures, that can lead to a more effective running of tourist enterprises and also contribute to the reinforcement of local entrepreneurship.
Keywords: 330